(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2014)
Components such as protein within the periplasmic space serve some vital purposes: such asÂ buffering against the outside environment, processing of essential nutrients for transport into theÂ cytoplasmic space, and cell wall biosynthesis. Dipeptide binding protein a (DppA) is a memberÂ of a family of ABC proteins and is involved in the transportation of potentially beneficialÂ dipeptides as nutrient source through the periplasmic space and into cell. DppA was successfullyÂ cloned into expression vectors and over expressed in Escherichia coli, extracted, purified, andÂ characterized. DppA was subjected to biophysical characterization using mass spectrometry.Â Mass spectrometry (ms) analysis and analytical ultra-centrifugation were used to evaluate theÂ recombinant DppAâ€™s molecular weight. The findings presented in this study highlighted theÂ ability to overexpress, extract and purify the recombinant DppA and reflect the differencesÂ techniques to asses its purity.